Leaf anatomy of young plants of erva-mate (Ilex paraguariensis A. St. Hill.) under different shading levels - Fermino Jr., Paulo Cesar Poeta; Fockink, Guilherme Diego (Scientia Agraria Paranaensis, 2017)
Light is one of the main environmental factors that influence plant growth and development. Erva-mate (Ilex paraguariensis A. St. Hill.) has an important socio-economical role in western Santa Catarina State, Brazil, to be produced on small farms and belongs to the cultural habits of various countries. The aim of this study was to analyze the changes in leaf anatomy of I. paraguariensis developed in a greenhouse under different levels of shading. Young plants were placed in a nursery under three levels of shading in greenhouse 50%, 70% and 0% (full sun) during eight months. Anatomical analyzes were performed on optical microscopy from temporary slides. Stomatal density showed no significant differences. Polar and equatorial diameters of stomata and width of stomatal pore were lower in most lighting conditions. The palisade parenchyma was thicker and with more elongated cells in higher light condition. I. paraguariensis exhibited anatomical plasticity, allowing acclimation at different levels of shading.